Soil characteristics pattern with the depth as affected by forest conversion to rubber plantation - C Agustina; S R Utami; S Sudarto (Brawijaya University, 2016)
This research was an attempt to study the impact of forest conversion to intensive rubber plantation on soil characteristics. We selected three landuses (forest, jungle rubber, and rubber plantation) in Bukit Duabelas and Harapan landscape, Jambi, and each repeated three times. Soil profiles were described and sampled at every 10 cm layer to 200 cm depth. Soil bulk density, pH, exchangeable basic cations content, and CEC were determined. The result showed that in three landuses, bulk density is relatively low in the upper 20 cm, but increased with depth. Clay content was lower in forest than other landuses, and increased with depth in forest and jungle rubber. In rubber plantation however, fine clay was accumulated at 60-140 cm depth. The CEC pattern with depth was in accordance to the clay content. There was no significant difference in soil pH between all landuses. In rubber plantation, soil pH was commonly higher in the surface, which probably due to liming activities. Sum of bases decreased with depth and tended to be generally lower in rubber plantation.